Targeting ferroptosis in prostate cancer management: molecular mechanisms, multidisciplinary strategies and translational perspectives - Hubo Yang; Xuefeng Zhang; Zongming Jia; He Wang; Jixiang Wu; Xuedong Wei; Yuhua Huang; Wenying Yan; Yuxin Lin (Journal of Translational Medicine)
Abstract Prostate cancer (PCa) is a kind of malignant solid tumor commonly observed among males worldwide. The dilemma of increasing incidence with therapeutic resistance has become the leading issue in PCa clinical management. Ferroptosis is a new form of regulatory cell death caused by iron-dependent lipid peroxidation, which has a dual role in PCa evolution and treatment due to the multi-omics cascade of interactions among pathways and environmental stimuli. Hence deciphering the role of ferroptosis in carcinogenesis would provide novel insights and strategies for precision medicine and personalized healthcare against PCa. In this study, the mechanisms of ferroptosis during cancer development were summarized both at the molecular and tumor microenvironment level. Then literature-reported ferroptosis-related signatures in PCa, e.g., genes, non-coding RNAs, metabolites, natural products and drug components, were manually collected and functionally compared as drivers/inducers, suppressors/inhibitors, and biomarkers according to their regulatory patterns in PCa ferroptosis and pathogenesis. The state-of-the-art techniques for ferroptosis-related data integration, knowledge identification, and translational application to PCa theranostics were discussed from a combinative perspective of artificial intelligence-powered modelling and advanced material-oriented therapeutic scheme design. The prospects and challenges in ferroptosis-based PCa researches were finally highlighted to light up future wisdoms for the flourishing of current findings from bench to bedside.